Design and development of an irrigation monitoring and control system based on blynk internet of things and thingspeak - Fahmy Rinanda Saputri; Ricardo Linelson; Muhammad Salehuddin; Danial Md Nor; Muhammad Imran Ahmad (PLoS ONE, 2025)
The scarcity of water resources exacerbated by climate change poses a major challenge for sustainable agriculture. This study presents an Internet of Things (IoT)-enabled irrigation system designed for real-time monitoring and precise water control. Using the Blynk platform and ThingSpeak for data management, the system integrates sensors for soil moisture, temperature, and humidity with a NodeMCU module to optimize irrigation practices. Initial results demonstrate the system’s effectiveness in improving water use efficiency and supporting sustainable agricultural practices, providing a low-cost, accessible solution for small and medium-scale farmers.